2004
DOI: 10.1063/1.1647282
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of magnetic properties by nitrogen implantation to Mn-implanted p-type GaN

Abstract: N and Mn ions were co-implanted into p-type GaN and subsequently annealed at 700–900 °C. Compared with Mn-implanted sample, the (Mn+N)-implanted sample revealed a larger ferromagnetic signal. This was attributed to the increase of Ga–Mn magnetic phases. Mn–N compounds, such as Mn6N2.58 and Mn3N2, decreased and the resistivity significantly increased, meaning a reduction of N vacancies. It is suggested that enhancement in ferromagnetic properties in the (Mn+N)-implanted GaN originated from the reduction of N va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…Mn is a well-behaved acceptor suitable for making p-type materials in Mn-doped InP and has small ionization energy in InP compared to the other transition metals [2]. DMS based on III-V and II-VI compound semiconductor such as GaAs, InAs, GaN, GaP, digital alloy system based on GaSb, quantum dot based on InMnAs, AlN, and ZnO have been studied since 1989 [3][4][5][6][7][8][9][10][11]. Among materials indicated above, GaAs and InAs with zinc blend structure which has three-dimensionally balanced and stabled lattice configuration have shown Curie temperature (T c ; 110-170 K [12]), which are confirmed by anomalous Hall effect (AHE) so as to show decisively the accomplishment of DMS without any other precipitates.…”
mentioning
confidence: 99%
“…Mn is a well-behaved acceptor suitable for making p-type materials in Mn-doped InP and has small ionization energy in InP compared to the other transition metals [2]. DMS based on III-V and II-VI compound semiconductor such as GaAs, InAs, GaN, GaP, digital alloy system based on GaSb, quantum dot based on InMnAs, AlN, and ZnO have been studied since 1989 [3][4][5][6][7][8][9][10][11]. Among materials indicated above, GaAs and InAs with zinc blend structure which has three-dimensionally balanced and stabled lattice configuration have shown Curie temperature (T c ; 110-170 K [12]), which are confirmed by anomalous Hall effect (AHE) so as to show decisively the accomplishment of DMS without any other precipitates.…”
mentioning
confidence: 99%
“…4 shows the corresponding FC (solid circle) and ZFC (open circle) curves with an applied field of 1000 Oe. As shown in this figure, the sample shows a ferromagnetic behavior persisting up to 350 K. The high Curie temperature of the sample may be caused by the ferromagnetic Mn 3 Ga phase, which is reported by many literatures [10][11][12][13]15].…”
Section: Resultsmentioning
confidence: 81%
“…The diffraction peaks locating at 2u = 38.48 and 2u = 44.38 correspond to the Mn 3 Ga phase, indicating that some implanted Mn-ions have combined with Ga atoms during the annealing process. Moreover, it has been reported that the Mn 3 Ga phase has high Curie temperature and plays an important role for the ferromagnetic properties of GaN:Mn systems [10][11][12][13]. Fig.…”
Section: Resultsmentioning
confidence: 98%
“…For (Mn+N)-implanted GaN, considering the XRD data in Fig. 2, the peak in the Mn 2p3/2 spectra corresponds to a Mn-N bond [10]. When the sample was annealed at 900 o C, a peak ( % ) located at a lower binding energy of approximately 3.0 eV was found.…”
Section: Resultsmentioning
confidence: 97%
“…3(b). For the as-implanted samples, the Ga 3d spectrum consists of Ga-N and Ga-O due to the implantation-induced loss of nitrogen atoms [10]. After annealing at 900 o C, a new peak could be separated at the higher bonding energy of 0.9 eV relative to the peak of the Ga-N bond.…”
Section: Resultsmentioning
confidence: 99%